Importance of biochemical parameters in order to predict clinical severity in patients diagnosed with Crimean-Congo haemorrhagic fever - Tartar, Ayse Sagmak; Balin, Safak Ozer; Catak, Zekiye; Akbulut, Ayhan; Demirdag, Kutbeddin (Walter de Gruyter Gmbh, 2019)
Objective: We aimed to investigate new biochemical indicators to predict the clinical course of patients following the diagnosis of Crimean-Congo haemorrhagic fever (CCHF). Material and methods: We retrospectively evaluated patients diagnosed with CCHF. They were divided into three groups based on a scoring system known as severity grading score in order to predict severity. Red cell distribution width (RDW), mean platelet volume (MPV), creatinine phosphokinase (CPK), alkaline phosphatase (ALP), glutamyl transferase (GGT) and C-reactive protein (CRP) levels were evaluated on the first day of admission. These biochemical parameters may predict the clinical course of our three patient groups. Results: In our study, there were 38 (70.4%) male and 16 (29.6%) female patients, and the mean age was 44.33 +/- 16.94 years. Based on our scoring system, 17 (31.4%), 30 (55.5%) and 7 (12.9%) patients were in group 1, 2 and 3, respectively. Statistically significant difference was observed between groups 1-3 and groups 2-3 for ALP values; however, a statistically significant difference was observed among all three groups for GGT values. Significant differences were not observed among the groups for RDW, MPW, CPK and CRP levels (p >0.05). Conclusion: ALP and GGT values can be used as auxiliary indicators to predict the clinical course for patients with CCHF. However, CPK, CRP, MPV and RDW values were not observed to be important for prognosis.
Keywords: Fever; Crimean-Congo haemorrhagic fever; RDW; MPV; ALP; GGT